2021
DOI: 10.1007/s10825-021-01753-0
|View full text |Cite
|
Sign up to set email alerts
|

Detecting nonclassicality and non-Gaussianity by the Wigner function and quantum teleportation in photon-added-and-subtracted two modes pair coherent state

Abstract: We introduce a new state called photon-added-and-subtracted two modes pair coherent state (PAASTMPCS) by simultaneously adding and subtracting photons to the different modes of a pair coherent state. Its nonclassical and non-Gaussian properties are strengthened via the negative values of its Wigner function as the numbers of adding and subtracting photons are increased. It indicates that the PAASTMPCS is an entangled state. When increasing the numbers of photon-added and photon-subtracted to a pair coherent st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 64 publications
1
16
0
Order By: Relevance
“…where B i, j,w ,C u and D i, j,w are given by Eqs. ( 9), ( 10) and (15). Analytical expressions in Eqs.…”
Section: Higher-order Three-mode Sum Squeezingmentioning
confidence: 99%
See 2 more Smart Citations
“…where B i, j,w ,C u and D i, j,w are given by Eqs. ( 9), ( 10) and (15). Analytical expressions in Eqs.…”
Section: Higher-order Three-mode Sum Squeezingmentioning
confidence: 99%
“…Given the available nonclassical states, we can enhance their degree of nonclassicality by using non-Gaussian operations such as adding or subtracting photons. For example, the degree of entanglement and squeezing can be enhanced by adding photons on the two-mode squeezed vacuum state [12], the two-mode squeezed thermal state [13], the two-mode displaced squeezed state [14], the pair coherent state [15], the trio coherent state [16,17], etc. More importantly, quantum tasks including quantum key distribution, quantum teleportation, quantum illumination as well as quantum state engineering can be improved by the photon addition and subtraction operations [15,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For two-and three-mode states, the addition and subtraction of photons to pair coherent states (PCSs) [21,22], two-mode squeezed vacuum state [23] and trio coherent states [24] have been studied [11,[25][26][27][28][29], and have provided many applications in quantum information and quantum state engineering [10,30]. For example, the addition and subtraction of photons can enhance the degree of squeezing [31,32], improve the degree of entanglement [33], the Einstein-Podolsky-Rosen correlation [31,34,35], increase the fidelity in quantum teleportation and the quality of quantum key distribution [31,36,37] in the proposed states. Moreover, the non-Gaussian property of proposed states by photons addition and subtraction [38,39] is also of great interest to researchers because it is closely related to the nonclassical properties of the states.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have suggested entanglement resources as quantum channels in teleportation processes (Nguyen & Truong, 2016;Truong et al, 2020Truong et al, , 2021Tran & Truong, 2022;Ho & Truong, 2022). In these studies, the class of photon-added and (or) -subtracted fields are used as entanglement resources to teleport the field states, which significantly improved the average fidelity and success probability of the teleportation.…”
Section: Introductionmentioning
confidence: 99%